TINDAK TUTUR EKSPRESIF PADA NOVEL SUNSET BERSAMA ROSIE KARYA TERE LIYE - Nova Irma Rahayu; Auzar Auzar; Elmustian Elmustian (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This article will describe the form and function of expressive speech acts found in the novel Sunset with Rosie by Tereliye. Speech acts belong to the branch of linguistics, namely pragmatics. Pragmatics is a branch of linguistics that examines and examines the structure of language, which is determined by the context and situation that form the basis of language usage and meaning study in each speaker. Voice Action is an action that uses the language that is used to convey the purpose of the speaker to the partner. Speech actions include speakers, listeners, readers, writers and discussed things. Speech acts are divided into locus, illocutionary and perlocution speech acts. Expressive speech acts are part of illocutionary speech acts. Expressive speech acts are speech acts that are spoken by speakers and intended as an evaluation of the things mentioned in the speech. The object selected in this study was the novel Sunset with Rosie by Tereliye. The novel was published in November 2011 with 426 pages. This novel is a bestselling novel based on the true story of a small family.Key Words: Pragmatics, expressive speech acts, novel